DEVELOPING OF TRIGRS (TRANSIENT RAINFALL INFILTRATION AND GRID-BASED REGIONAL SLOPEâSTABILITY ANALYSIS) INTO TRIGRS MAP FOR LANDSLIDE SUSCEPTIBILITY MAPPING - Yunarto, Yunarto (GEOMATIKA, 2016)
ABSTRACTTRIGRS is a modeling program for slope stability against the occurrence of landslide and pore water pressure changes due to infiltration of rainfall. There are two problems in TRIGRS operation. Firstly, whole data must have no mistake before being executed in TRIGRS. Secondly, TRIGRS is not completed by spatial visualization based on Geographic Information System (GIS), so it needs GIS e.g. MapInfo, ArcGIS, and ILWIS to visualize its result. The purpose of this paper is present the result of development of TRIGRS MAP by using integrated mapping technique between MapInfo and Visual Basic. Implementation of TRIGRS MAP for Bandung Regency area has generated a landslide susceptibility map of the area. By using TRIGRS MAP, user can avoid a mistake in data initialization and directly visualize its result as a map. Thus, TRIGRS MAP can be used to process data from other area for creating the landslide susceptibility map more easily and efficientlyÂ